Biomolecular simulations of membranes: physical properties from different force fields. - Siu, Shirley Weng In; Vacha, Robert; Jungwirth, Pavel; Böckmann, Rainer (Journal of Chemical Physics, 2008)
Phospholipid force fields are of ample importance for the simulation of artificial bilayers, membranes, and also for the simulation of integral membrane proteins. Here, we compare the two most applied atomic force fields for phospholipids, the all-atom CHARMM27 and the united atom Berger force field, with a newly developed all-atom generalized AMBER force field (GAFF) for dioleoylphosphatidylcholine molecules. Only the latter displays the experimentally observed difference in the order of the C2 atom between the two acyl chains. The interfacial water dynamics is smoothly increased between the lipid carbonyl region and the bulk water phase for all force fields; however, the water order and with it the electrostatic potential across the bilayer showed distinct differences between the force fields. Both Berger and GAFF underestimate the lipid self-diffusion. GAFF offers a consistent force field for the atomic scale simulation of biomembranes.